Mitigating Cyberbullying in Primary and Secondary Education: A Systematic Literature Review on the Mediating Role of Digital Literacy - Dini Rakhmawati; Lina Putriyanti; Agung Prasetyo; Agus Setiawan (Scidacplus, 2026)
The integration of digital technology in education increases the risk of cyberbullying, which threatens students’ psychosocial well-being. This research examined the effectiveness of school-based intervention by focusing on the digital competence and online safety education as the moderating variables. The applied method of the current research is a systematic literature review, SLR, with PIRSMA 2020 protocol guidelines. Researchers conducted a systematic search in the Scopus database for articles published between 2023 and 2025. From a total of 100 identified records, the researchers applied a rigorous screening process and selected 10 final studies that met the inclusion criteria. The synthesized data reveal school-based intervention with digital literacy integration provided effective cyberbullying rate reduciton than the conventional monitoring approaches. The key findings identify digital competence as a crucial mediator that shapes students’ ethical behavior and resilience in cyberspace. This study emphasizes the importance of a structured online safety curriculum within school guidance and counseling programs.